Adaptation to coastal soils through pleiotropic boosting of ion and stress hormone concentrations in wild Arabidopsis thaliana. Issue 1 (19th July 2021) - Busoms, Silvia; Terés, Joana; Yant, Levi; Poschenrieder, Charlotte; Salt, David E.
Summary: Local adaptation in coastal areas is driven chiefly by tolerance to salinity stress. To survive high salinity, plants have evolved mechanisms to specifically tolerate sodium. However, the pathways that mediate adaptive changes in these conditions reach well beyond Na + . Here we perform a high‐resolution genetic, ionomic, and functional study of the natural variation in Molybdenum transporter 1 ( MOT1 ) associated with coastal Arabidopsis thaliana accessions. We quantify the fitness benefits of a specific deletion‐harbouring allele ( MOT1 DEL ) present in coastal habitats that is associated with lower transcript expression and molybdenum accumulation. Analysis of the leaf ionome revealed that MOT1 DEL plants accumulate more copper (Cu) and less sodium (Na + ) than plants with the noncoastal MOT1 allele, revealing a complex interdependence in homeostasis of these three elements. Our results indicate that under salinity stress, reduced MOT1 function limits leaf Na + accumulation through abscisic acid (ABA) signalling. Enhanced ABA biosynthesis requires Cu. This demand is met in Cu deficient coastal soils through MOT1 DEL increasing the expression of SPL7 and the copper transport protein COPT6 . MOT1 DEL is able to deliver a pleiotropic suite of phenotypes that enhance salinity tolerance in coastal soils deficient in Cu. This is achieved by inducing ABA biosynthesis and promoting reduced uptake or better compartmentalization of Na +, leading to coastal adaptation.